2008
DOI: 10.1093/pch/13.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Risk indicators for depressed mood in youth: Limited association with Aboriginal cultural status

Abstract: The recognition that Aboriginal cultural status is not independently associated with moderate or severe depressed mood in youth after full multivariate adjustment allows policy makers to acknowledge that mental health disparity prevention is possible because the determinants of health (ie, education) are modifiable (in comparison with Aboriginal cultural status).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…The disparities between the health status of Aboriginal youth and of non-Aboriginals are flagrant (cf. Elton-Marshall et al, 2011;Larkin et al, 2007;Lemestra et al, 2008;MacNeil, 2008;Raphael, 2009;Shields et al, 2004;Smith, Findlay, & Crompton, 2010;Tjepkema & Wilkins, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The disparities between the health status of Aboriginal youth and of non-Aboriginals are flagrant (cf. Elton-Marshall et al, 2011;Larkin et al, 2007;Lemestra et al, 2008;MacNeil, 2008;Raphael, 2009;Shields et al, 2004;Smith, Findlay, & Crompton, 2010;Tjepkema & Wilkins, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it was reported that 8.5% of Saskatoon youth and 19% of Aboriginal youth living in Saskatoon attending grades 5 through 8 experienced suicidal ideation in the previous year (12). In the present study, the same questionnaire was completed by First Nations youth in grades 5 through 8 living on reserve.…”
mentioning
confidence: 68%
“…It was unexpected that mood and anxiety disorders in general were not elevated for Indigenous Australian and Maori populations, given the context of elevated rates of mental health service usage (Abas et al, 2003;Abas et al, 2008; Australian Institute of Health and Welfare, 2011), psychological distress (Australian Institute of Health and Welfare, 2011;Cunningham and Paradies, 2012;Gubhaju et al, 2013;Ministry of Health, 2015), alcohol and/or substance use (Baxter et al, 2006;Indig et al, 2010;Indig et al, 2011;Marie et al, 2008;Simpson et al, 2003), hospitalised rates of self-harm (Ministry of Health, 2011; Steering Committee for the Review of Government Service Provision, 2014), and suicide in these groups (Beals et al, 2005). Another study found that after adjusting for covariates (such as gender and parental education), Canadian Aboriginal status was not significantly linked to depressed mood in a large sample of young people (N= 4,093; Lemstra et al, 2008). These results may therefore reflect genuine outcomes where Indigenous people are not at significantly higher risk of some psychiatric disorders than other groups.…”
Section: Discussionmentioning
confidence: 99%